Taxonomic considerations on the genus Zabrus Clairville, 1806 (Coleoptera, Carabidae) in Iberian Peninsula - A.V. Anichtchenko (Кавказский энтомологический бюллетень, 2008)
The iberian species of the genus Zabrus Clairville, 1806 are revised. A new subgenus and three new species are described: Cantabrozabrus subgen. n.; Zabrus (Iberozabrus) uhagoni sp. n. (Cuenca, Guadalajara, Teruel); Zabrus (Iberozabrus) fuentei sp. n. (Teruel); Zabrus (Iberozabrus) prietoi sp. n. (Peña Trevinca). A new reorganization of the genus as well as several changes in the status of different species are proposed: Z. (Iberozabrus) laurae Toribio, 1989, stat. rest.; Z. (Iberozabrus) arragonensis Heyden, 1883, stat. rest.; Z. (Iberozabrus) cameranus Arribas, 1994 = Z. (Iberozabrus) laurae Toribio, 1989, syn. n.; Z. (Iberozabrus) seidlitzi gredosanus Jeanne, 1970 = Z. (Iberozabrus) seidlitzi Schaum, 1864, syn. n.; Z. (Iberozabrus) eserensis Bolivar, 1918 = Z. (Iberozabrus) obesus (Audinet-Serville, 1821), syn. n